Foresight-based Business Model Design: Presentation and Validation of a Conceptual Model - Salman Hosseini Safa; Safar Fazli; Hakem Ghasemi; Ali Khaleghi (‫مدیریت بازرگانی)
Objective A business model is a strategic concept that shows how to create, deliver, and obtain value. Although business models change along with environmental changes, they need innovation, anticipation, exploratory thinking, and momentum to overcome the acceleration of changes. Business model innovation requires design insight. Foresight is a systematic and collaborative process for building the future, which focuses on making businesses future-oriented through consultation, knowledge acquisition, and visioning. Existing business model design patterns pay little attention to the design space and the future. Moreover, existing foresight frameworks do not pay enough attention to business model design. Therefore, studies indicate the need to provide a comprehensive model to consider the changes in the environment, existing uncertainties, and future situations in business model design. This research was carried out with the aim of solving the gap in the literature and presenting a conceptual model of business model design based on foresight.